Diversity and structure of the fish population in Lake Maabo, Chad, Central Africa - LALEYE, PHILIPPE A.; CHIKOU, ANTOINE; LEDEROUN, DJIMAN (My University, 2023)
Diversity and structure of the fish population of Lake Maabo in Chad, Central Africa The aim of the study is to inventory the fish species in Lake Maabo and to study the spatio-temporal organization of the population. To achieve this objective, artisanal catches using various fishing gears were monitored between January 2016 and December 2019, and experimental fishing was carried out between January and December 2019 using a bacterium of gillnets with different mesh sizes (5, 10, 15, 20, 25, 30 and 35 mm). A list of the species inventoried was drawn up and diversity was assessed using diversity indices (Shannon and Piélou equitability). In total, 34 species divided into 27 genera, 18 families, and 7 orders were inventoried for all fisheries combined, of which 33 species were present in the experimental catches. Clchlidae and Mochokidae (5 species: 14.70 %), Mormyridae and Alestidae (4 : 11.76 %), Schilbeidae and Cyprinidae (2 : 5.88 %) were the most represented. The other families each had one species. There is an equal-representation of individuals of each species. The present study added 22 species to the lake's fish list.
Keywords: Ichthyofauna; Logone; fish; distribution